Pembuatan Teknologi Tepat Guna Sebagai Upaya Memecahkan Permasalahan Lingkungan Di Desa Kedungpari - Agung Satria Bimantara; Farhan Kusuma Waradana (Politeknik Kampar, 2023)
Lack of awareness and attention to environmental management is the main cause of environmental pollution, not only in cities but also in villages. Making appropriate technology in the form of trash cans from used tire aims to reduce waste of used car tires and also as a learning medium for the people in Kedungpari Village to process existing used tires so that they can become something useful for the surrounding environment. The creation of these trash cans also increases the awareness of the village community not to dispose of waste as they please. In the environment where the 20 KKN-T groups were held this time, it was held in Kedungpari Village, Mojowarno District, Jombang Regency, where in this environment there was a lot of unused used tire waste.